HIGH-ORDER MOMENTS OF THE SUM OF RANDOM VARIABLES USING THE METHOD OF CHARACTERISTIC FUNCTIONS (Web of Teachers: Inderscience Research, 2025)
The problem of determining the order moment of the sum of random variables (r.v.) using the method of characteristic functions (ch.f.) is studied in the article. order moment of the sum of independent and dependent r.v.-es subject to the exponential law with the parameter is found.